2022
DOI: 10.1111/eci.13863
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PCSK9 inhibitors on remnant cholesterol and lipid residual risk: The LIPID‐REAL registry

Abstract: Background Monoclonal antibodies that inhibit the proprotein convertase subtilisin/kexin type 9 (PCSK9) reduce low‐density lipoprotein cholesterol (LDLc) by 55%, regardless of baseline treatments. Nonetheless, the effect of other lipid parameters, such as cholesterol remnants or, the so‐called lipid residual risk, is unknown. Methods Multicenter and retrospective registry of patients treated with PCSK9 inhibitors from 14 different hospitals in Spain. Before and on‐treatment lipid parameters were recorded. Resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Similarly, in the PREDIMED study, in overweight or obese subjects at high cardiovascular risk, TG and RC serum levels, but not LDL-C, were associated with cardiovascular outcomes [44]. Recently, a retrospective registry of real-world patients treated with PCSK9 inhibitors demonstrated a positive effect on RCs and lipid residual risk beyond LDL-C reductions [55].…”
Section: Study Study Population Resultsmentioning
confidence: 96%
“…Similarly, in the PREDIMED study, in overweight or obese subjects at high cardiovascular risk, TG and RC serum levels, but not LDL-C, were associated with cardiovascular outcomes [44]. Recently, a retrospective registry of real-world patients treated with PCSK9 inhibitors demonstrated a positive effect on RCs and lipid residual risk beyond LDL-C reductions [55].…”
Section: Study Study Population Resultsmentioning
confidence: 96%
“…More recently, in a post hoc analysis that evaluated data from five randomized controlled trials (RCT), ezetimibe + statins resulted in greater reductions in RC compared to statin monotherapy in both statin-naïve and statin-taking patients [ 34 ]. The multicenter LIPID-REAL registry study, involving 652 patients treated with PCSK9 inhibitors (evolocumab or alirocumab), showed significant reductions in RC (from 29.88 mg/dL to 27.30 mg/dL), TC/HDL ratio, TG/HDL ratio, and the TG-to-glucose index at a median follow-up of 187.5 days, with more pronounced decreases observed in patients whose baseline RC exceeded 30 mg/dL [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since RC and hsCRP are actively implicated in the formation of atherosclerosis beyond the influence of LDL-C, treatment with RC-lowering and anti-inflammatory drugs for minimizing the risk of cardiovascular diseases has previously been explored. According to recent research, individuals treated with proprotein convertase subtilisin/kexin type 9 inhibitors exhibited benefits with respect to decreased cholesterol remnants and lipid residual risk, beyond the reductions in LDL-C [40]. Specifically, a combined analysis of three randomized controlled trials suggested that alirocumab therapy resulted in a 42.1-52.5% decrease in RC levels compared with placebo [41].…”
Section: Discussionmentioning
confidence: 99%